Tinnitus Prevalence, Associated Characteristics, and Treatment Patterns among Adults in Saudi Arabia - Ahmad A. Alanazi (Audiology Research)
Tinnitus affects millions of people around the world and causes significant negative impacts on their quality of life (QoL). Tinnitus is rarely examined in Saudi Arabia. This study aimed to estimate the prevalence of tinnitus among adults, explore their experience with tinnitus, investigate the impact of tinnitus on their QoL, and discover their tinnitus management methods. A descriptive cross-sectional study design was performed utilizing a non-probability purposive sampling technique and a face-to-face in-person administered questionnaire. Descriptive statistics and a chi-square test were used to assess the data and find any correlation between the variables. Out of 4860 adults, 320 (males: n = 172; females: n = 148; age range = 18–90 years) had tinnitus, mainly described as a daily, gradual, continuous, whistling, and ringing tinnitus in both ears. Tinnitus prevalence was estimated at 6.54% with a slight predominance in males (6.9%) compared with females (6.2%). Most of the participants were unaware of the cause of their tinnitus. The modal value of the severity of tinnitus signals was severe for both genders. The modal value of the impact of tinnitus on the QoL was moderate for males and severe for females. Sleep, social activities, quiet settings, and concentration were largely affected by tinnitus. Significant associations (p < 0.05) between the impact of tinnitus on the QoL and risk factors, such as gender, age, hearing loss, and hyperacusis were determined. Also, the impact of tinnitus on the QoL was significantly associated (p < 0.05) with the duration of complaints and the severity of tinnitus signals. Approximately, 61% of the participants did not use any tinnitus treatment, while the remaining participants usually used hearing aids, medications, and counseling to manage their tinnitus. By increasing awareness, establishing standard practice, developing guidelines for managing tinnitus, expanding access to suitable interventions, and carrying out additional research, adults living with tinnitus in Saudi Arabia will have better support and, ultimately, an enhancement of their overall well-being.